2015
DOI: 10.1038/ncomms6973
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome sequencing reveals the mutational spectrum of testicular germ cell tumours

Abstract: Testicular germ cell tumours (TGCTs) are the most common cancer in young men. Here we perform whole exome sequencing of 42 TGCTs to comprehensively study the mutational profile of TGCT. The mutation rate is uniformly low in all of the tumours (mean 0.5 mutations per megabase [Mb]) as compared to the common cancers, consistent with the embryological origin of TGCT. In addition to expected copy number gain of chromosome 12p and mutation of KIT we identify recurrent mutations in the tumour suppressor gene CDC27 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
185
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(209 citation statements)
references
References 65 publications
22
185
0
2
Order By: Relevance
“…S2). In addition to gain of 12p in individual samples, SCNAs were consistent with available historical data (van Echten et al 1995;Faulkner et al 2000;Looijenga et al 2000;Skotheim and Lothe 2003;McIntyre et al 2007;Litchfield et al 2015), notably recurrent pan-TGCT gains of Chromosomes 7, 8, 22, and X, and losses of Chromosomes 4,5,10,11,13,18, and Y (Fig. 1); also evident are the relative gains of Chromosomes 19 and 22 in SEs relative to NSEs (van Echten et al 1995;Summersgill et al 1998).…”
Section: Series Descriptionsupporting
confidence: 60%
“…S2). In addition to gain of 12p in individual samples, SCNAs were consistent with available historical data (van Echten et al 1995;Faulkner et al 2000;Looijenga et al 2000;Skotheim and Lothe 2003;McIntyre et al 2007;Litchfield et al 2015), notably recurrent pan-TGCT gains of Chromosomes 7, 8, 22, and X, and losses of Chromosomes 4,5,10,11,13,18, and Y (Fig. 1); also evident are the relative gains of Chromosomes 19 and 22 in SEs relative to NSEs (van Echten et al 1995;Summersgill et al 1998).…”
Section: Series Descriptionsupporting
confidence: 60%
“…Our results as well as other studies [3,9,24] indicate that activation of the MAPK and/or PI3K pathways by somatic point mutations is one of the main driving forces of GCT development regardless of histological subtype or site of origin. We showed that the function of activating MTOR mutations may be effectively suppressed by a specific inhibitor suggesting that these mutations can be exploited to treat at least a subset of CNS GCTs that shows resistance to conventional chemotherapy.…”
Section: Clinical Associationmentioning
confidence: 48%
“…1; Supplementary Tables S14, S15). Recently, a whole exome sequencing study on 42 tGCTs was published [9]. When the exome mutation profiles are compared with our current study, few genes are shared between the two cohorts except KIT and KRAS, which were found mutated at a comparable frequency.…”
Section: Mutational Profiles Of Cns and Testicular Gctsmentioning
confidence: 86%
“…Other recognized risk factors for TGCT include a history of undescended testis (UDT) and other testicular abnormalities such as hypogonadism and microlithiasis 45,46 . Elevated TGCT risk is also associated with Down syndrome (trisomy 21) 47 and Klinefelter syndrome (47XXY karyotype) 48 and, intriguingly, somatic gains of both chromosomes 21 and X are frequently observed in TGCTs 49 . Furthermore, cooccurrence in families of ovarian germ cell tumour and TGCT has also been recurrently reported, suggesting shared oncogenic pathways 50 .…”
mentioning
confidence: 98%